The Development of "Esago" Application as a Form of Improving the Quality and Prosperity for Farmers - Palilingan, Verry Ronny; Togas, Peggy Veronica (International Journal of Information Technology and Education, 2022)
In North Sulawesi Province, there are many agricultural lands with superior food commodities. However, there are many problems that make agricultural production less than optimal in North Sulawesi Province. With the rapid developments in the field of information technology, the researchers created a system, namely an E-Commerce application called EsaGo. The EsaGo application is an Android-based application that provides agricultural education and farming tutorials that farmers can learn. The research method used is the System Development Life Cycle method. SDLC consists of the problem investigation, feasibility study, system analysis, system design, implementation system, and system testing phases. The research method is carried out in stages, starting with looking for problems to the testing stage. Before the system is published, the system will be tested by developers and experts in their field, to test the functionality of the tool. The final result obtained is the Esago application which has the ability to rent farmer locations and display farmer locations within a certain radius inputted by consumers. The results of trials on 10 farmer users and 15 consumers show that this Esago is useful (Perceived Usefulness) and easy to use (Perceived Ease of Use) for buying and selling agricultural products for farmers and consumers.